Sea Transportation Services in the Framework of Good Governance - Chairul Insani Ilham; Mangatur T Brenhard; Ferdinand Pusriansyah (IWJ : Inland Waterways Journal, 2020)
The problem of sea transportation on Panjang Island, Batam City, is that it is inadequate for marine transportation such as a lack of safety buoys, excessive passenger capacity, and the absence of passenger safety insurance so that it greatly threatens the safety of passengers and is troubling for parents whose children are studying across the board. The purpose of this study is to determine the marine transportation services in Panjang Island, Batam City in the framework of governance, and to determine the characteristics of good governance in sea transportation services in Panjang Island in the framework of good governance. This type of research is qualitative descriptive, then analyzed qualitatively, namely by data reduction analysis techniques, data presentation, and drawing conclusions (verification). Research location in Panjang Island, Sijantung Subdistrict, Galang District, Batam City. There were 9 research informants and 1 person as the key informant. The theory used in this research is the theory of good governance, namely the public government and the private sector. The results of this study indicate that sea transportation services on Panjang Island move due to the interaction of the three actors involved first, the government, namely the Department of Transportation which provides safety equipment and the Education Office as an actor involved in providing transportation assistance for Panjang Island students who are passengers. Second, the private sector, namely the owner of sea transportation, which provides sea transportation. Third, the people of Panjang Island as passengers and connoisseurs of sea transportation services. If seen from the principles of good governance, the responsiveness of the government already exists but it is not sustainable and there is no supervision from the government and community participation is still very low so that their aspirations are not conveyed to the government and transportation facilities owned by the private sector are also not effective and efficient for used as a means of public transportation. The conclusion of this study is that the interaction of the three actors involved in sea transportation services on Panjang Island has not been running according to good governance so that sea transportation is not suitable for public transportation because it threatens the safety of passengers or connoisseurs of sea transportation services.